Final de la vida y notas en bioética médica - Ivone, Vitulia (2012)
End of life and changes in medical bioethicsThe issue of the end of life includes —necessarily— an analysis of human dignity in its social and legal dimension as a parameter and value of the cultural history of countries and societies. The vagueness of this term has created, in particular, many difficulties in the effort to define its boundaries. In particular, the use of human dignity to understand the dynamics of the end of life faces the issue of medical paternalism and theory of informed consent in the doctor-patient relationship.